A survey of reverse mergers in the Chinese stock market. Issue 1 (24th January 2019) - Xin, Qingquan; Li, Ruitao; Wong, Sonia
Abstract : Purpose: The purpose of this paper is to provide an introduction to the reverse mergers (RMs) conducted in the Chinese stock market by summarizing the regulatory system, surveying the literature on RMs and analyzing the major characteristics of 161 RM cases. Design/methodology/approach: This paper introduces the characteristics and evolution of the regulatory framework governing RM activity in China. Then the paper reviews relevant academic studies on the RMs in China and other countries. Finally, the paper identifies and discusses the major characteristics of 161 RM cases in the Chinese stock market from 2006 to 2016. Findings: Private companies that go public via RMs in China not only have superior asset quality but also demonstrate good accounting and stock price performance after listing, and these results are unlike those of studies on the quality of RMs in other countries. Research limitations/implications: This paper is based on a survey of 161 RM cases in China's stock market, with the major characteristics of the RMs being identified and analyzed. The limitations of previous studies and suggestions for further research are discussed. Originality/value: This paper suggests that the relative superior performance of RMs in the Chinese stock market is caused by the interplay of market forces and regulatory oversight. The Chinese regulator's pragmatic and flexible approach plays an important role in formulating regulatory policies that respond to the changing macroeconomic environment and financial markets.